Investigation of the acoustic properties of bio luffa fiber and composite materials - GENÇ, GARİP (ELSEVIER, 2015)
Considering the adverse effects of petroleum-based materials on nature, finding and developing new materials as alternatives to these chemical materials become a necessity in practice. On the other hand, these new materials need characterization to be considered and effectively used in practical applications. The acoustic properties of luffa bio fiber and composite materials are investigated in this study. First, the preparation of various luffa test samples and the method for acoustic characterization of the luffa samples is presented. Then, the acoustic absorption properties of both luffa fiber and composite materials are identified using the impedance tube method. After that, the transmission loss levels of the same luffa samples are determined. All the results are evaluated and the acoustic performances of luffa materials are highlighted. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Biomaterials; Porous materials; Luffa fibers; Luffa composites; Sound absorption; Transmission loss; MECHANICAL-PROPERTIES; FLAX-FIBER; GLASS